The Number of Osteoblast and Osteoclast during Orthodontic Tooth Movement after Preconditioned Gingiva Mesenchymal Stem Cell Allogeneic Transplantation in vivo - Diah Savitri Ernawati, - (Ektodermal Displazi Grubu, 2022)
Malocclusion can affect the quality of life related to oral health. A novel technique to expedite orthodontic tooth movement (OTM) in order to minimize treatment length and the side effects. Under orthodontic fore, MSCs transplantation might hypothetically accelerate the bone remodeling process, resulting in OTM acceleration. To investigate the number of osteoclasts and osteoblasts in the tension side during OTM after transplantation of normoxic or hypoxic preconditioned allogeneic gingival mesenchymal stem cells in vivo. The OTM animal model was 48 male rabbits (Oryctolagus cuniculus) aged 6 months with body weight about 3-4 kg. There were 4 experimental groups in this study: control negative group (C-): injected with PBS without OTM, positive control group (C+): 50g OTM with 20µL PBS injection, treatment group 1 (T1): 50g OTM with 20µL GMSCs normoxia in PBS, treatment group 1 (T2): 50g OTM with 20µL GMSCs hypoxia in PBS. The injection was done in afflicted mandibular gingiva using µL small needle syringe with local infiltration technique. Every sample then was sacrificed after day 7, 14, and 28 respectively. The number of osteoblasts and osteoclasts in the alveolar bone during OTM was determined by hematoxylin and eosin staining. In T2 group, osteoblast was significantly enhanced on day 14 and 28 but not osteoclast number during OTM. There was significant different in osteoclast and osteoblast number between groups (p<0.05) GMSCs hypoxia preconditioned escalate osteoblast number but not decrease the osteoclast number in the tension side during orthodontic tooth movement in vivo.